1985
DOI: 10.1017/s0022278x00000173
|View full text |Cite
|
Sign up to set email alerts
|

Land Use and Agricultural Productivity in Zimbabwe

Abstract: Given a continuation of current trends, with increasing population growth and declining food production, Southern Africa (excluding South Africa) which could nearly feed itself during 1979–81, will be only 64 per cent self-sufficient by the turn of the century. Zimbabwe has a particularly important rôle to play in trying to prevent such a disaster. It is by far the most important exporter of food and cash crops in the region, and has been allocated the task of co-ordinating a food-security strategy for the nin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

1989
1989
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 3 publications
1
29
0
1
Order By: Relevance
“…37 Another estimate was that in Mashonaland, less than one-third of arable land was actually being used. 38 Furthermore, these large farmers were not producing very much. The Rhodesian National…”
Section: Criteria 3: Production and Productivitymentioning
confidence: 99%
“…37 Another estimate was that in Mashonaland, less than one-third of arable land was actually being used. 38 Furthermore, these large farmers were not producing very much. The Rhodesian National…”
Section: Criteria 3: Production and Productivitymentioning
confidence: 99%
“…The extensive powers inherited under the Emergency Powers Act, the Law and Order (Maintenance) Act, and other legislation, as well as the massive police and intelligence apparatus built by Rhodesian governments were maintained and even expanded (Weitzer 1984;Ncube 1991). The ZANU(PF) government justified the maintenance of the state's repressive capabilities in terms of the threat posed by South Africa and disgruntled whites.…”
Section: Zanu (Pf) Ideology: Constraints Of a Negotiated Independencementioning
confidence: 99%
“…Numerous calculations were made, from those of the 1982 Transitional Plan to the 1991 World Bank report which concluded that at least three million hectares of commercial land in the high potential regions were underused. As the report commented, 'This 3 million hectares is equal to the total amount of land resettled during the 1980s (1991:45; also see Cliffe 1986;Weiner et al 1985;Weiner 1988;Moyo et al 1989). …”
Section: The Resettlement Programme: Plans and Politicsmentioning
confidence: 99%
“…It also provides 45% of the country's exports, providing employment for 70% of Zimbabwe's population (Weiner, Moyo, Munslow, & O'Keefe, 1985;Maiyaki, 2010). The agricultural land is divided into five main agro-ecological regions which relate to climatic conditions, soils, and to the appropriate farming systems adopted.…”
Section: Introductionmentioning
confidence: 99%